Bisphenol A exhibits cytotoxic or genotoxic potential via oxidative stress-associated mitochondrial apoptotic pathway in murine macrophages. (December 2018) - Huang, Fu-Mei; Chang, Yu-Chao; Lee, Shiuan-Shinn; Ho, Yung-Chyuan; Yang, Ming-Ling; Lin, Hui-Wen; Kuan, Yu-Hsiang
Abstract: Bisphenol A (BPA) is primarily used in production of polycarbonate plastics and epoxy resins including plastic containers. BPA is an endocrine disruptor and supposes to induce asthma and cancer. However, so far only a few evidences have shown the BPA-induced toxic effect and its related mechanism in macrophages. BPA demonstrated cytotoxic effect on RAW264.7 macrophages in a concentration and time-dependent manner. BPA induces necrosis, apoptosis, and genotoxicity in a concentration-dependent manner. Phosphorylation of cytochrome C (cyto C) and p53 was due to mitochondrial disruption via BCL2 and BCL-XL downregulation and BAX, BID, and BAD upregulation. Both caspase-dependent, including caspase-9, caspase-3, and PARP-1 cleavage, and caspase-independent, such as nuclear translocation of AIF, pathways were activated by BPA. Furthermore, generation of reactive oxygen species (ROS) and reduction of antioxidative enzyme activities were induced by BPA. Parallel trends were observed in the effect of BPA on cytotoxicity, apoptosis, genotoxicity, p53 phosphorylation, BCL2 family expression exchange, caspase-dependent and independent apoptotic pathways, and ROS generation in RAW264.7 macrophages. Finally, BPA-exhibited cytotoxicity, apoptosis, and genotoxicity could be inhibited by N-acetylcysteine. These results indicated that the toxic effect of BPA was functioning via oxidative stress-associated mitochondrial apoptotic pathway in macrophages. Graphical abstract: Highlights: BPA exhibits cytotoxicity, apoptosis, and genototixicty in macrophages. BPA induces p53 phosphorylation and stabilization, mitochondrial dysfunction, exchange of BCL2 family. BPA induces mitochondrio-nuclear translocation of AIF and cleavage of PARP-1, pro-caspase-3, and pro-caspase-9. BPA induces ROS generation and reduced antioxidant enzymes activities. N-Acetylcysteine reduces BPA-induced cytotoxicity, apoptosis, genotoxicity.